What Works When? Exploring Contingency in Software Development Methodology - Sheffield, Jim; Lemétayer, Julien; Ahimbisibwe, Arthur (School of Management Working Papers, 2011)
In project management „one size does not fit all‟. Matching the methodology to the needs of a particular project is essential in managing cost, quality and schedule. Because project personnel tend to favour the methodology they are most experienced in, and numerous methodologies are available on the market, objective guidance is required to select a methodology that leads to project success. This research engaged with members of the PRINCE2, PMI and Agile communities via local interviews and an international survey. Factors in the project and project environment (organisation, industry, etc) were identified that predicted the software development methodology that fits. The results also reveal that methodology fit, experience level and market uncertainty are significant predictors of project success.